Dissection of genotype‐by‐environment interaction and simultaneous selection for grain yield and stability in faba bean (Vicia faba L.). (13th February 2023) - Gela, Tadesse S.; Khazaei, Hamid; Podder, Rajib; Vandenberg, Albert
Abstract: Increasing faba bean production is indispensable to supply the growing demand for plant‐based protein on the global scale. A thorough understanding of genotype (G) × environment (E) interaction (GEI) patterns is critical to developing high‐yielding varieties with wider adaptation. Thirteen faba bean genotypes were evaluated in 15 environments during 2019–2020 in western Canada to estimate their yield stability using different stability statistics. The combined analysis of variance and additive main effects and multiplicative interaction (AMMI) analysis revealed that G, E, and GEI effects were highly significant ( p  < 0.001), indicating differential responses of the genotypes across the environments, enabling the stability analysis. The result of the model comparison found the best linear unbiased prediction (BLUP) to outperform AMMI models. The BLUP‐based biplot of the weighted average of absolute scores (WAASB) stability and mean grain yield (GY) identified AO 1155 (Navi), 1089‐1‐2, 1310‐5, DL Tesoro, and 1239‐1 as high‐yielding and stable genotypes. The correlation analysis revealed that most of the stability parameters had a strong association with GY and with each other, indicating that they should be used in combination with one another to select genotypes with high yield. Overall, the WAASB superiority index and the average sum of ranks of all stability statistics identified the same genotypes in terms of high‐yielding and stability, and genotype AO 1155 is considered the most stable and highest yielding among the tested genotypes. Genotypes with stable yields across environments would be beneficial for faba bean genetic improvement programs globally. Core Ideas: Stability analysis was estimated using 13 faba bean genotypes over 15 site‐years. The different stability methods described genotypic performance in different ways. The majority of stability models showed a strong rank correlation with grain yield. AMMI and BLUP analyses revealed a highly significant G × E interaction, with BLUP outperforming AMMI. Overall, the employed stability statistics identified AO 1155 as the highest yielding and most stable genotype.